Why More Agencies and Researchers Should Embrace the Upcoming NIBRS Transition: Contributions and Promise of the NIBRS Data - Lantz, Brendan (American journal of criminal justice, 2022)
When the NIBRS data were introduced by the FBI, they were welcomed as representing a potential revolution in U.S. crime statistics. More than two decades later, however, participation in NIBRS remains limited. In the coming months and years, however, the FBI will transition from the UCR Summary Reporting System (SRS) to NIBRS. Once completed successfully, the ability for researchers and practitioners to use the data will be unprecedented. But the NIBRS data are incredibly useful for both agencies and researchers regardless of these changes. Within this context, the current article explores the past contributions and future promise of the NIBRS data.